EVALUATION OF BIOCHEMICAL AND HISTOCHEMICAL CHANGES FOLLOWING THE COMBINED TREATMENT OF MERCURY AND CADMIUM IN A FRESH WATER CAT FISH, CLARIAS BATRACHUS (LINN) - Arya, Alpana (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The main objective of this study was to determine the combined effects of cadmium (Cd) and mercury (Hg) at sub-lethal concentrations for 32 days on histochemical localization of heavy metals and on serum biochemical parameters including serum glutamic-pyruvic transaminase (SGPT) enzyme activity; glucose, triglyceride, cholesterol and total protein concentrations in Clarias batrachus. Methods: Histochemical demonstration of Hg and Cd salts in liver and kidney was determined by sulphide–silver method and SGPT, glucose, triglyceride and cholesterol in the serum were measured using the standard protocols provided in the commercial kits purchased from Reckon diagnostics Pvt. Ltd., India. Results: Serum SGPT, glucose, triglyceride, cholesterol and total protein levels were significantly altered in fish exposed to Cd or Hg salt alone. However, combined exposure of Cd and Hg normalized all the above mentioned biochemical parameters. Histochemical analysis demonstrated enormous amount of metals in the liver and kidney tissues exposed to Hg and Cd alone. Mercury accumulation in C. batracus was comparatively more than that of cadmium in both the tissues. Conclusion: While exposure Hg or Cd adversely altered the biochemical parameters in the test catfish, following the combined exposure of both the metals, the concentrations of metal accumulation were decreased in both the tissues of C. batracus.